Análisis metagenómico de microorganismos con potencial tolerante y resistente a metales pesados presentes en islas de recursos del Caribe Colombiano. - Herrera Calderón, Andrea Carolina (Universidad Antonio Nariño, 2023)
The bacteria from resource islands can adapt to extreme conditions in semi-arid regions, where concentrations of heavy metals have already been found in the soil. Therefore, the objective of this study is to determine the resistance and tolerance to heavy metals in bacteria under the canopy of resource islands in the Colombian Caribbean. Through a metagenomic approach, genes related to tolerance and resistance to heavy metals were identified in the soil, and it was found that the abundance of these genes was favored by the wet season and the presence of vegetation.